The Role of Islamic Rural Banks in the Development and Strengthening of Micro, Small and Medium Enterprises in the Agribusiness Sector in Riau Province - Fahrial; Tibrani; Desvaeryand, Rega (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
The problem of Micro, Small and Medium Enterprises in the agribusiness sector in Riau Province is business capital. This research aims to analyze the role of Islamic Rural Banks in the development and strengthening of Micro, Small and Medium Enterprises in the agribusiness sector in Riau Province. The method used in this research is empirical research. The results of the research explain that the average Micro, Small and Medium Enterprises in the agribusiness sector in Riau Province have characteristics in the age group of 38 to 43 years with junior high school level education and 1 to 7 years of business experience. There are two Sharia Rural Banks in Riau Province, namely BPRS Berkah Dana Fadhlillah and BPRS Hasanah. Bank service variables and types of financing products have a significant effect on the development and strengthening of Micro, Small and Medium Enterprises in the agribusiness sector in Riau Province. The strategy adopted by BPRS Berkah Dana Fadhlillah and BPRS Hasanah is a faster financing process so that they can compete with conventional banks as well as product innovation and affordable administrative costs.